Physical Culture for the Integral Education of University Students: A Critical Constructivist Approach (RIAF. International Journal of Physical Activity, 2024)
The objective of this study is to thoroughly examine how physical culture influences the overall development of university students while employing a critical constructivist approach to challenge conventional educational frameworks. To address this question, a quantitative study with a descriptive-correlational approach was conducted, involving a sample of 1,000 students enrolled at the University of Guayaquil.The results of this study clearly demonstrate that physical culture has a significantly positive influence on the overall development of undergraduate university students. This statement is supported by observed improvements in participants across physical, cognitive, emotional, and social dimensions. From a physical standpoint, there is notable progress in the health and fitness of students who actively engage in activities related to physical culture.Cognitively, students who integrate physical culture into their daily routines show advancements in concentration and academic performance. In terms of emotional well-being, participation in physical culture activities is associated with greater overall satisfaction among students, suggesting that physical activity benefits emotional health.It is important to highlight that students who participate in physical culture activities experience much lower stress levels compared to those who do not. Physical culture can serve as a tool for stress management, which, in turn, helps achieve a better balance between academic demands and emotional pressures.The findings of this study underscore the importance of incorporating physical culture into the university environment from a critical constructivist perspective. This approach not only enhances the overall education of students but also strengthens their physical and emotional well-being while promoting critical reflection on the interactions between physical activity and student life as a whole.
Keywords: Physical Culture; Comprehensive training; college students; Critical Constructivist Approach